Comprehensive experimental study on a transcritical CO2 ejector-expansion refrigeration system. (1st November 2017) - Zhu, Yinhai; Li, Conghui; Zhang, Fuzhen; Jiang, Pei-Xue
Highlights: The ejector and cooling performances of a transcritical CO2 ejector-expansion system were studied. A new coefficient was defined to estimate the deviation between current operating state and a steady state. The primary flow pressure has an optimal value only for relatively high back pressure conditions. Both the entrainment ratio and COP decrease with an increase in the coefficient of mass balance. Abstract: A comprehensive experimental study on the ejector and cooling performances of a transcritical CO2 ejector-expansion system is presented. The ejector performance of the entrainment ratio, pressure lift ratio, and efficiency were investigated under various primary flow pressure, secondary flow pressure, and back pressure conditions. A new coefficient of mass balance, β, was introduced based on the liquid mass balance in and/or out of the vapor–liquid separator, which was able to estimate the deviation between current operating state and a steady state. The experiment results show that the coefficient of performance (COP) ratio of the ejector-expansion refrigeration system to the basic system decreases from 18.9% to −11% with the coefficient of mass balance increasing from −0.1 to 0.1. Both the entrainment ratio and COP decrease with an increase in the coefficient of mass balance.